TEARS OF THE FASCIA CRURIS AT THE ATTACHMENT TO THE ACHILLES TENDON. Issue 21 (12th October 2014) - Webborn, N; Morrissey, D; Chan, O
Abstract : Aim: To describe the clinical presentation, ultrasound imaging characteristics, and the time to recovery of tears of the fascia cruris. The fascia cruris encloses the posterior structures of the calf and connects to the paratenon and Achilles tendon.1 2 Injuries to this structure have not previously been described. Methods: Retrospective review of 13 fascia cruris tears in 9 patients (6 male and 3 female, mean age 35.52 year, range 11–48) with identified using diagnostic ultrasound, after presenting with Achillodynia. Results: 9 athletic subjects were identified and presented at a mean of 4.5 weeks (range 0.5–12) after the symptom onset. Subjects were typically highly active comprising four sub-3 hr marathon runners, three high level triathletes and two tennis players. The left Achilles was more commonly injured than right (7:4) and lateral side more than medial (6:4) with one bilateral presentation. Clinically there was swelling and well localised tenderness over the tear site and from the mid to upper portion of the Achilles. 7 of the 11 (63.6%) had functional over-pronation. US appearances of the tear included a hypo-echoic area extending from the medial or lateral border of the Achilles anteriorly along the anatomical plane of the fascia cruris. Average return to activity was 5.2 weeks (range 1–22 weeks). Subjects presenting later had longer recovery (r=0.4) but all subjects returned to full activity. Conclusions: This is the first description of the clinical details and sonographic findings of a tear to the fascia cruris at its attachment to the Achilles tendon and paratenon. It tends to occur at the confluence of the fascia cruris onto the paratenon and Achilles. This needs to be considered as a cause of Achillodynia in athletes and early diagnosis aids early return to activity.